Innovation and growth: The Australian Productivity Commission's policy void?. (June 2016) - Dalitz, Robert
Governments' economic policies need to be based on a coherent view of the role of innovation and productivity in sustaining growth. This article analyses advice on fostering innovation from Australia's main statutory economics adviser, the Productivity Commission. It argues that the Productivity Commission's comprehensive 2007 report, Public Support for Science and Innovation, contributed to a policy vacuum hampering government support for innovation for nearly a decade. First, within the Productivity Commission's understanding of innovation was a contradiction between its required policy targeting criteria and the impossibility of meeting these criteria. Second, the resulting stance on innovation policy was at odds with research and theory on the drivers of innovation and hence growth – particularly innovation systems theories and those based on evolutionary economics. The ensuing innovation policy vacuum suggests that the Productivity Commission placed the abstract ideological 'purity' of neoclassical economic theory above empirical exploration of how government can best support Australia's future economic development. Since late 2015, moves to fill this policy vacuum have included a Senate inquiry, a government department restructure, and the creation of a new Innovation and Science statutory advisory board. Whether these initiatives foster sustained innovation will depend on the extent to which they adopt approaches based on innovation systems or evolutionary economics, and transcend the static neoclassical mindset espoused by the Productivity Commission.